India's investment climate voices of Indian business - Ferrari, Aurora (World Bank E-Library Archive, 2009)
The Indian economy : robust growth but challenges remain -- Manufacturing : investment climate obstacles to productivity growth and employment generation -- Unorganized manufacturing : facilitating entry to the formal sector by removing obstacles to growth and productivity -- Retail sector : facilitating the emergence of large players to boost productivity and employment -- Software and ITES sector : productivity improvements key to continued growth and competitiveness -- Reducing inequalities between states by improving the investment climate